TRACKING TYPE III RADIO BURST SOURCES IN THE SOLAR CORONA BY HELIOGRAPHIC MEANS - Koval, A. A.; Stanislavsky, A. A.; Konovalenko, A. A.; Volvach, Ya. S. (Одеські астрономічні публікації, 2014)
We present the preliminary results of heliographic measurements of solar type III radio bursts in the lowfrequency range (16.5-33 MHz) using the UTR-2 radio heliograph. The radio astronomy tools permit us to obtain two-dimensional spatial structures of burst sources in dependence of frequency and time. Each heliogram consists of 40 pixels (beams) as a result of the serial sweep in UV-plane wherein signals of each beam are recorded in a dynamic spectrum with both high temporal ( 2.482 ms) and top spectral ( 4 kHz) resolutions. The rate of output heliograph is one image per 3 seconds. Over a session in April, 2013 many type III radio and IIIb-III bursts were observed. On the heliograms the source motion direction in the upper corona is clearly detectable. The heliogram features are discussed.